2008
DOI: 10.1371/journal.pbio.0060289
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Secretase Represents a Therapeutic Target for the Treatment of Invasive Glioma Mediated by the p75 Neurotrophin Receptor

Abstract: The multifunctional signaling protein p75 neurotrophin receptor (p75NTR) is a central regulator and major contributor to the highly invasive nature of malignant gliomas. Here, we show that neurotrophin-dependent regulated intramembrane proteolysis (RIP) of p75NTR is required for p75NTR-mediated glioma invasion, and identify a previously unnamed process for targeted glioma therapy. Expression of cleavage-resistant chimeras of p75NTR or treatment of animals bearing p75NTR-positive intracranial tumors with clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 75 publications
2
76
0
Order By: Relevance
“…Recent studies of malignant gliomas found that inhibition of ␥-secretase cleavage of p75 results in a decrease in glioma invasion and an increase in survival (47). In this case, generation of the ICD in glioma cells produces a more invasive phenotype, suggesting that there are changes in gene expression as a result of p75 cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of malignant gliomas found that inhibition of ␥-secretase cleavage of p75 results in a decrease in glioma invasion and an increase in survival (47). In this case, generation of the ICD in glioma cells produces a more invasive phenotype, suggesting that there are changes in gene expression as a result of p75 cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…BTIC self-renewal (secondary sphere-forming) assays were performed under neural stem cell conditions as described previously (3,32). Spheres were dissociated and viable cells were counted.…”
Section: Self-renewal Assaymentioning
confidence: 99%
“…Patient-derived BTICs from newly diagnosed (BT73, BT108, BT126, BT127, BT134, BT164) and recurrent (BT119, BT143, BT147) tumors were implanted into the brain of mice as described previously (3,32,34). Mice were monitored weekly and tumor growth was assessed using the IVIS-200 Optical in vivo imaging system, MRI, or by IHC at designated timepoints.…”
Section: Characterization Of Btics In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Many molecules have been implicated in malignant glioma invasion (Salhia et al, 2006;Johnston et al, 2007;Wang et al, 2008), but the molecular mechanisms that regulate MGC invasion remain elusive. This study shows a novel functional-screening assay to identify promoters of invasion.…”
Section: Discussionmentioning
confidence: 99%